Intensification of the wastewater treatment process for its secondary use in food enterprises - M. A. Novikova; M. V. Goncharov; D. V. Syzrancev; G. V. Alekseev (Современная наука и инновации, 2023)
To date, the issues of resource conservation are of increasing concern to mankind, in this regard, the issues of the secondary use of raw materials and auxiliary materials are becoming promising. On average, food enterprises use about 50 m3 of water per se, this water in addition to the main technological process is used for auxiliary operations. The article considered standard methods of wastewater treatment from pollution and modern ways to improve the quality of treatment.